A resource flow-based branch-and-bound algorithm to solve fuzzy stochastic resource-constrained project scheduling problem - Alipouri, Yaghoub (Soft computing (Berlin, Germany), 2021)
In this paper, a resource flow-based branch-and-bound procedure is designed to solve the well-known resource-constrained project scheduling problem under the mixed uncertainty of fuzziness and randomness (FS-RCPSP). The objective is to minimize the expected makespan of the project subject to precedence and resource constraints. The proposed branch-and-bound can be employed to obtain optimal solutions and also can be truncated in order to find promising near optimal solutions. The depth-first strategy is utilized for constructing the search tree, and earliest start time (EST) concept is adopted for selecting a node for further branching while traversing the tree down to the leaves. The performance of developed branch-and-bound is benchmarked against CPLEX and SADESP across an extensive set of 960 problems. The results returned by the proposed algorithm show experimentally its effectiveness to solve the FS-RCPSP.